Credit Constraints, Heterogeneous Firms, and International Trade - Manova, Kalina (Review of Economic Studies, 2013)
Financial market imperfections severely restrict international trade flows because exporters require external capital. This article identifies and quantifies the three mechanisms through which credit constraints affect trade: the selection of heterogeneous firms into domestic production, the selection of domestic manufacturers into exporting, and the level of firm exports. I incorporate financial frictions into a heterogeneous-firm model and apply it to aggregate trade data for a large panel of countries. I establish causality by exploiting the variation in financial development across countries and the variation in financial vulnerability across sectors. About 20%–25% of the impact of credit constraints on trade is driven by reductions in total output. Of the additional, trade-specific effect, one-third reflects limited firm entry into exporting, while two-thirds are due to contractions in exporters' sales. Financially developed economies export more in financially vulnerable sectors because they enter more markets, ship more products to each destination, and sell more of each product. These results have important policy implications for less developed nations that rely on exports for economic growth but suffer from weak financial institutions.